PHYSICOCHEMICAL AND MICROBIAL ANALYSIS OF THE INDUSTRIAL WASTES IN A COPPER AND STEEL FACTORY IN NNEWI, ANAMBRA STATE NIGERIA - Igbokwe, Adaolisa Millicent; Ugwu, Chidiebere Emmanuel; Dike, Charles Chijioke; Mbachu, Nancy Amara; Maduka, Hugh Clifford Chima (Journal of Biomedical Investigation, 2023)
Background: Waste from industrial processes in modern civilization contributes to water pollution, particularly contaminating groundwater through leaching and industrial effluents. Aim of study: The aim of this study was to evaluate the toxicological and environmental impacts of a copper and steel factory wastes on the physicochemical and microbial qualities of the liquid effluent, water and soil around a copper and steel factory. Methodology: A purposive sampling technique was employed for the study. The samples were grouped into 6 groups: 1 (soil samples from the factory), 2 (effluent discharge from factory), 3 (water sample from boreholes in the factory), 4 (water sample from borehole around the factory), 5 (soil sample from non-industrial site) and 6 (water sample from borehole, non-industrial site). Physicochemical properties (turbidity, electrical conductivity, pH, total hardness, total dissolved solids) and microbial analysis were determined using known standard methods. Analysis of the results was done using known standard methods and the results were statistically analyzed. Results: The results showed that all physicochemical properties were within WHO permissible limit except turbidity levels in factory effluent and boreholes (P < 0.05), suggesting the samples from the factory may contain suspended and colloidal matter, and microorganisms. Microorganisms such as E.coli, Streptococcus Spp., Coliform Spp. and Klebsiella spp. were found in samples. Conclusion: The industrial processes of the factory may have polluted the borehole water, thereby making it unsafe for both drinking and domestic use.